A method for producing ultrafine copper-based pre-alloyed powder

By surface dispersing the submicron metal powder in an acidic solution and introducing the copper salt solution for replacement reaction, ultrafine copper-based prealloy powder with a core-shell structure is solved, and the problem of difficulty in treating iron powder below the submicron level is achieved in the prior art, efficient copper coating and antioxidant effects are achieved, and suitable for industrial production.

CN119747651APending Publication Date: 2025-04-04CHONGQING YOUYAN ZHONGYE NEW MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411963130.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing copper-clad iron powder preparation methods are difficult to deal with iron powder below the submicron level, resulting in problems such as spontaneous combustion and oxidation during the preparation process, limiting the industrial application of nano-clad iron powder.

Method used

By performing surface dispersion treatment on the submicron metal powder in an acidic solution, the copper salt solution is introduced for replacement reaction, and an ultrafine copper-based prealloy powder with a core-shell structure is formed. The method includes stirring, replacement reaction and drying steps, regulating the thickness and uniformity of the copper cladding layer, and avoiding agglomeration and oxidation of the powder.

Benefits of technology

It realizes effective copper coating on the surface of submicron iron powder, improves the antioxidant and physical properties of the powder, and has the excellent properties of iron and copper, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747651A_ABST
    Figure CN119747651A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal material composite functional powder, and in particular, relates to a method for producing ultrafine copper-based pre-alloyed powder. The technology includes the following steps: S1, selecting submicron metal powder for surface dispersion treatment in an acidic solution, controlling the stirring rate, reaction time and pH, and regulating the surface activity of the submicron metal powder; S2, introducing a copper salt solution to carry out a replacement reaction; S3, washing and drying to obtain a submicron ultrafine copper-based pre-alloyed powder with a core-shell structure. The integrated and controllable preparation of the inner core submicron metal powder and the nano copper-based coated metal powder is realized. A layer of copper film can be coated on the surface of the submicron iron powder, so that its antioxidant capacity is greater than that of conventional passivated submicron iron powder, and it has a series of excellent physical properties of iron and copper, has a good market application prospect, the preparation process is simple and controllable, the copper coating layer can be effectively controlled, and can better meet the needs of large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material composite functional powders, and in particular relates to a method for producing ultrafine copper-based pre-alloyed powder. Background Art

[0002] Affected by the requirements of high-end equipment manufacturing materials, the performance requirements of raw metal powders are also getting higher and higher. The composite of metal powders is one of the current key research directions of powder metallurgy technology. Composite treatment of metal powders can improve the comprehensive performance of metal powders, prepare powder products with new performance, and provide ideal raw materials for the development of downstream powder metallurgy products. Studies have shown that by coating a tiny powder on the surface of another powder particle or dispersing it in it, several powders with different properties can be processed into composite powders. This composite powder can not only improve the performance of a single powder, but also have a composite synergistic effect.

[0003] Copper-coated iron powder is a composite powder with a copper coating on the surface of iron powder. It has the advantages of high electrical conductivity and thermal conductivity and strong corrosion resistance of the copper-based shell and high strength of the iron-based core. It can effectively improve the problems of uneven organization and component segregation of traditional copper-iron mixed powders, and is widely used in powder metallurgy fields such as oil-containing bearings, diamond tools and friction fields. With the innovation of application needs and technology, the powder scale is no longer limited to the micron level and is transitioning to the nanometer level. However, due to the high activity, large specific surface area, and easy agglomeration of nanopowders, and the extremely unstable nano-iron powder in the air, which is easy to oxidize violently and cause spontaneous combustion, the preparation and preservation of iron-based nanopowders are relatively difficult, and the market application prospects are still unclear, which seriously restricts the technical development and industrial application of nano copper-coated iron powders. Submicron ultrafine powder materials have both the high strength of micron-level powders and the high activity of nanopowders, becoming an intermediate material for the transition from micron level to nanometer level, which has aroused widespread market demand and has good market application prospects.

[0004] At present, the methods suitable for large-scale preparation of copper-clad iron mainly include mechanical coating, chemical replacement, and surface deposition. However, when the powder scale becomes sub-nanometer level, the mechanical coating method is no longer applicable due to the high activity and spontaneous combustion of sub-micron iron powder. The chemical replacement method uses the difference in metallic activity between copper and iron to replace the copper ions in the copper salt solution with copper element and then coat it on the surface of the iron powder. By changing the reaction conditions and adding additives, the thickness, uniform density and dispersibility of the copper coating layer can be effectively controlled. The preparation of nanopowders is also highly controllable and can be mass-produced in industry.

[0005] The instruments required for the surface deposition method are relatively simple and easy to operate, and have been widely used. The surface deposition method is to first disperse the particles uniformly in the solution, and then use chemical means such as replacement reaction, disproportionation reaction and reduction reaction to form a coating phase, which is then deposited on the surface of the particles to form a coated powder.

[0006] In order to prevent the spontaneous combustion of ultrafine iron powder and prepare high-performance ultrafine copper-coated iron powder, researchers have made many improvements. The Chinese patent with patent publication number CN1936066A discloses a passivation method for ultrafine iron powder. The passivation gas forms a protective oxide film on the surface of the ultrafine iron powder to achieve the passivation effect and avoid spontaneous combustion. This method is a method worth learning from. The Chinese patent with patent publication number CN1817509A discloses a production method for copper-coated iron composite powder. The copper in the copper sulfate solution is replaced by micron-level iron powder and deposited on the surface of the iron powder to form a copper film to achieve the coating of the iron powder, but the coating process of submicron-level iron powder is no longer applicable. The Chinese patent with patent publication number CN105251996A discloses a core-shell structure copper-coated nano-composite powder and its preparation method and application. Nano-iron powder is added to a copper acetate-dimethylformamide solution, the surface of the nano-iron powder is modified by organic matter, and then copper is replaced to obtain a copper-coated iron composite powder. The copper-coated iron composite powder has stable properties and strong antioxidant ability, but the presence of organic matter will affect the interface bonding performance between copper and iron and the coating effect.

[0007] Most of the methods disclosed so far are for the preparation of micron copper-coated iron powder, which does not have the spontaneous combustion hazard caused by the high activity and strong oxidizing property of submicron iron powder, and there is no report on the integrated preparation of submicron iron powder and copper-coated iron powder. Therefore, the existing conventional methods for preparing copper-coated iron can only process iron powder above micron level to prepare copper-coated iron powder, but cannot process iron powder below micron level (submicron or nanometer) to prepare copper-coated iron powder. Summary of the invention

[0008] The purpose of the present invention is to provide a method for producing ultrafine copper-based pre-alloyed powder, which can realize the production of inner core submicron metal powder and nano copper-based coated metal powder.

[0009] The method for producing the ultrafine copper-based pre-alloyed powder comprises the following steps: S1. Select submicron metal powder and perform surface dispersion treatment in an acidic solution, control the stirring rate, reaction time and pH, and regulate the surface activity of the submicron metal powder; S2, introducing a copper salt solution to carry out a replacement reaction; S3, washing and drying to obtain a submicron ultrafine copper-based pre-alloyed powder with a core-shell structure.

[0010] Furthermore, in step S1, the submicron metal powder includes ultrafine iron powder.

[0011] Furthermore, in step S1, the submicron metal powder includes at least one of the following materials: reduced iron powder, atomized iron powder, with a particle size of ≤50 μm and a purity of ≥95%.

[0012] Furthermore, in step S1, the pH of the acidic solution is ≤4, and the acidic solution includes at least one of the following materials: dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid.

[0013] Furthermore, in step S1, the stirring speed is 500 rpm to 1000 rpm, the reaction time is 1 to 5 min, and the pH range is 2 to 5.

[0014] Furthermore, in step S2, the copper salt solution includes at least one of the following materials: copper sulfate, copper chloride, copper nitrate, and copper acetate, the copper mass concentration is 40 g / L to 60 g / L, and a surfactant is added.

[0015] Furthermore, the surfactant includes sodium dodecyl sulfate with a concentration of 0.5 g / L to 2 g / L.

[0016] Furthermore, in step S2, the mass concentration, introduction time and reaction time of the copper salt solution are controlled so that the copper coating thickness is 20 nm to 1000 nm and the particle size is 10 nm to 50 μm.

[0017] Furthermore, in step S2, the copper salt solution is introduced for 1 to 5 minutes, the replacement reaction time is 1 to 5 minutes, and the replacement reaction temperature ranges from 20°C to 60°C.

[0018] Furthermore, in step S3, washing includes centrifugal filtration, and drying includes one of the following methods: drying reduction, vacuum drying, and freeze drying, and the drying time is 2 to 10 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for producing a core-shell structured ultrafine copper-based pre-alloyed powder, especially an ultrafine copper-based pre-alloyed powder, which realizes the integrated and controllable preparation of a core submicron metal powder and a nano copper-based coated metal powder. The submicron metal core is obtained by activating the surface of the ultrafine iron powder, a copper salt solution is introduced into a reactor to react with the activated submicron metal core, the coating thickness and uniformity are adjusted by regulating the introduction of the copper salt solution and the reaction time, and the oxidation and agglomeration of the powder are regulated by vacuum drying and freeze drying, thereby realizing the integrated and controllable preparation of the ultrafine copper-based pre-alloyed powder.

[0020] A layer of copper film can be coated on the surface of submicron iron powder, making its antioxidant ability greater than that of conventional passivated submicron iron powder, and making it have a series of excellent physical properties of iron and copper. It has good market application prospects, the preparation process is simple and controllable, the copper coating layer can be effectively controlled, and it can better meet the needs of large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a flow chart of a method for producing ultrafine copper-based pre-alloyed powder.

[0022] The names of the components in the figure are: 1. Reactor; 2. Submicron metal powder introduction device; 3. Reactor agitator; 4. Container outlet lead-out device; 5. Copper salt solution container; 6. Copper salt solution agitator; 7. Reactor exhaust port; 8. Reactor discharge port. DETAILED DESCRIPTION

[0023] The present invention is further described below through specific embodiments in conjunction with the accompanying drawings, but the present invention is not limited thereto. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0024] definition Micrometer: Micrometer is a unit of measurement for length. The length of 1 micrometer is one millionth of 1 meter and one thousandth of 1 millimeter.

[0025] Nanometer: Nanometer is a unit of measurement for length, 1 nanometer = 0.001 micrometer.

[0026] Submicron: Submicron is a new concept in the materials industry, referring to a series of ultrafine materials from micron to nanometer scale.

[0027] Reduced iron powder: Reduced iron powder is a gray or black powder mainly containing elemental iron.

[0028] Atomized iron powder: Atomized metal powder refers to tiny particles made by using high-speed and high-pressure airflow, high-speed rotating centrifugal force or other mechanical methods to cause molten metal flow to rapidly impact, separate and condense. The atomized iron powder here refers to tiny particles of iron.

[0029] Ultrafine iron powder: particle size D 50 Iron powder with a particle size smaller than that of ordinary iron powder (10μm). It includes reduced iron powder, atomized iron powder and nano iron powder. The preparation methods of reduced iron powder, atomized iron powder and nano iron powder are different, and the powder morphology obtained is different.

[0030] Submicron metal powder: metal powder with a particle size less than 50μm. Micron powder has a particle size less than 100μm; nano powder has a particle size less than 100nm; submicron powder is between nano powder and micron powder.

[0031] A method for producing ultrafine copper-based pre-alloyed powder comprises the following steps: S1. Select submicron metal powder and perform surface dispersion treatment in an acidic solution, control the stirring rate, reaction time and pH, and regulate the surface activity of the submicron metal powder.

[0032] Specifically, add the prepared acidic solution into the stirred reactor 1, Figure 1 The dotted line in the reactor 1 indicates the solvent added to the reactor 1. Submicron metal powders of different specifications are selected. In this embodiment, 100g to 135g of submicron iron powders of different morphologies and particle sizes are selected as precursors and sent into the reactor 1 through the submicron metal powder introduction device 2 for surface pretreatment reaction to prepare submicron metal iron powder; wherein, the selected submicron iron powder includes ultrafine iron powder, and the actual submicron iron powder can include at least one of the following materials: reduced iron powder, atomized iron powder, particle size ≤50μm, purity ≥95%. The acidic solution is a dilute acid aqueous solution with a certain pH, and there is no special requirement for purity. It includes at least one of the following materials: dilute sulfuric acid, dilute hydrochloric acid, dilute nitric acid aqueous solution, and the pH of the acidic solution is ≤4. The surface dispersion treatment includes controlling the stirring speed, reaction time and pH regulation of the reactor stirrer 3, the stirring speed is 500rpm to 1000rpm, the reaction time is 1 to 5min, and the pH range is 2 to 5. Submicron iron powder is used as a raw material for preparing ultrafine copper-based pre-alloyed powder. As a precursor, it is fed into a reactor 1 to which an acidic solution has been added through a submicron metal powder introduction device 2 for surface pretreatment to prepare a submicron metal core; monodisperse particles are formed in the acidic solution of the reactor 1, and the surface activity of the ultrafine iron powder is regulated by controlling the stirring rate, reaction time and pH of the reactor 1, and the gas in the reactor 1 is discharged through the exhaust port 7 of the reactor.

[0033] S2, introducing a copper salt solution to carry out a replacement reaction; Specifically, the copper salt solution prepared in the copper salt solution container 5 is introduced into the submicron metal colloid whose surface has been pretreated through the container outlet outlet device 4. Figure 1 The dotted part in the copper salt solution container 5 represents the copper salt solution. Specifically, the prepared copper salt solution is introduced into the reactor 1 with the surface pretreatment completed and stirred. A large number of electrons in the reaction system are obtained by copper ions and converted into copper atoms, which are deposited on the surface of the submicron metal iron powder, and the copper metal replacement coating is performed to obtain a super copper-based pre-alloyed powder colloid; the copper deposition thickness, uniformity and dispersibility on the surface of the iron powder are adjusted by controlling the mass concentration of the copper salt solution, the introduction and the reaction time.

[0034] The copper salt solution includes at least one of the following materials: copper sulfate, copper chloride, copper nitrate, copper acetate, and the copper mass concentration is 40g / L to 60g / L. A surfactant is added, and the surfactant includes sodium dodecyl sulfate, and the concentration is 0.5 g / L to 2g / L to improve dispersibility and prevent agglomeration and sedimentation. The mass concentration, introduction time and reaction time of the copper salt solution are controlled so that the copper coating thickness is 20nm to 1000nm, the particle size is 10nm to 50μm, and the morphology of the obtained ultrafine copper-based pre-alloyed powder includes but is not limited to spherical, quasi-spherical, polyhedral, linear, and rod-shaped. The introduction time of the copper salt solution is 1 to 5min, the replacement reaction time is 1 to 5min, and the replacement reaction temperature ranges from 20℃ to 60℃.

[0035] S3, washing and drying to obtain a submicron ultrafine copper-based pre-alloyed powder with a core-shell structure.

[0036] Washing includes but is not limited to centrifugal filtration, and drying is one of the following methods: drying reduction, vacuum drying, and freeze drying, and the drying time is 2 to 10 hours.

[0037] The completely coated product, i.e., the obtained ultra-copper-based pre-alloyed powder colloid, is discharged from the reactor discharge port 8 of the reactor 1, and then washed and dried to obtain a submicron ultra-fine copper-based pre-alloyed powder with a core-shell structure. Specifically, the ultra-fine copper-based pre-alloyed powder after the reaction is completely completed is washed multiple times, and the washing liquid is centrifuged to be neutral, and the treated powder is dried to obtain an ultra-fine copper-based pre-alloyed powder with a core-shell structure.

[0038] Submicron iron powder is used to obtain a submicron metal core through surface pretreatment. The surface pretreatment can be metal activation on the surface of the submicron iron powder to form monodisperse particles, and a large number of electrons are formed in the solution. Then the configured copper salt solution is introduced into the submicron metal colloid that has been surface pretreated. The metal ions in the metal salt solution obtain a large number of electrons in the solution and are quickly deposited on the surface of the submicron metal core to generate a core-shell structure ultrafine copper-based pre-alloyed powder, realizing the integrated and controllable preparation of the core submicron metal powder and the nano copper-based coated metal powder.

[0039] Embodiment 1: S1: Select and weigh materials according to the scheme settings, weigh 100g of reduced iron powder raw material, pour it into the reactor 1 filled with sulfuric acid solution with a pH value of 1.5, the reactor speed is 800rpm, the reaction time is 2min, and the iron powder particles are dispersed to improve its surface activity.

[0040] S2: Weigh 60g of copper sulfate pentahydrate (CuSO4•5H2O) and dissolve it in 380mL of deionized water in a copper salt solution container 2 to obtain a copper salt solution. Sodium dodecyl sulfate is added to the copper salt solution at the same time to a concentration of 2g / L. Stir vigorously at a speed of 600rpm and adjust the pH to 2.5 by adding an acidic solution. The prepared copper salt solution is a copper sulfate solution. The prepared copper sulfate solution is introduced into the reactor 1 within 5min for replacement reaction. The specific introduction time of the copper salt solution is 5min, the replacement reaction time is 3min, and the replacement reaction temperature range is between 20℃ and 60℃.

[0041] S3: After the reaction is completed, the ultrafine copper-based pre-alloyed powder is washed 4 times by centrifugation with deionized water until it is neutral, and the washed powder is dried and reduced at 600° C. for 3 h to obtain the ultrafine copper-based pre-alloyed powder.

[0042] Embodiment 2: S1: Select and weigh materials according to the scheme settings, weigh 120g of ultrafine iron powder raw material, pour it into the reactor 1 filled with sulfuric acid solution with a pH value of 2, the speed of the reactor 1 is 1000rpm, the reaction time is 5min, and the iron powder particles are dispersed to improve its surface activity.

[0043] S2: Weigh 70g of copper sulfate pentahydrate (CuSO4•5H2O) and dissolve it in 350mL of deionized water in a copper salt solution container 2 to obtain a copper salt solution. Sodium dodecyl sulfate is added to the copper salt solution at the same time to a concentration of 1g / L. Stir vigorously at a speed of 500rpm, and adjust the pH to 3 by adding an acidic solution. The prepared copper salt solution is a copper chloride solution. The prepared copper chloride solution is introduced into the reactor 1 within 2min for replacement reaction. The specific introduction time of the copper salt solution is 2min, the replacement reaction time is 5min, and the replacement reaction temperature range is between 20℃ and 60℃.

[0044] S3: After the reaction is completed, the ultrafine copper-based pre-alloyed powder is washed 4 times by centrifugation with deionized water until it is neutral, and the washed powder is dried in a freeze drying oven for 10 hours to obtain the ultrafine copper-based pre-alloyed powder.

[0045] Embodiment 3: S1: Select and weigh materials according to the scheme settings, weigh 135g of atomized iron powder raw material, pour it into reactor 1 filled with hydrochloric acid solution with a pH value of 4, the speed of reactor 1 is 500rpm, the reaction time is 1min, and the iron powder particles are dispersed to improve its surface activity.

[0046] S2: Weigh 80g of copper sulfate pentahydrate (CuSO4•5H2O) and dissolve it in 330mL of deionized water in a copper salt solution container 2 to obtain a copper salt solution. Sodium dodecyl sulfate is added to the copper salt solution at the same time to a concentration of 0.5 g / L. Stir vigorously at a speed of 600rpm and adjust the pH to 5 by adding an acidic solution. The prepared copper salt solution is a copper nitrate solution. The prepared copper nitrate copper solution is introduced into the reactor 1 within 2min for replacement reaction. The introduction time of the copper salt solution is 1min, the replacement reaction time is 2min, and the replacement reaction temperature range is between 20℃ and 60℃.

[0047] S3: After the reaction is completed, the ultrafine copper-based pre-alloyed powder is washed 4 times by centrifugation with deionized water until it is neutral, and the washed powder is dried in a vacuum drying oven at 60° C. for 2 h to obtain the ultrafine copper-based pre-alloyed powder.

Claims

1. A method for producing ultrafine copper-based pre-alloyed powder, characterized in that: The following steps are involved: S1. Select submicron metal powder and perform surface dispersion treatment in an acidic solution, control the stirring rate, reaction time and pH, and regulate the surface activity of the submicron metal powder; S2, introducing copper salt solution to carry out replacement reaction; S3, washing and drying to obtain a submicron ultrafine copper-based pre-alloyed powder with a core-shell structure.

2. The method for producing ultrafine copper-based pre-alloyed powder according to claim 1, characterized in that: In the step S1, the submicron metal powder includes ultrafine iron powder.

3. The method for producing ultrafine copper-based pre-alloyed powder according to claim 1 or 2, characterized in that: In the step S1, the submicron metal powder includes at least one of the following materials: reduced iron powder, atomized iron powder, with a particle size of ≤50 μm and a purity of ≥95%.

4. The method for producing ultrafine copper-based pre-alloyed powder according to any one of claims 1 to 3, characterized in that: In step S1, the pH of the acidic solution is ≤4, and the acidic solution includes at least one of the following materials: dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid.

5. The method for producing ultrafine copper-based pre-alloyed powder according to any one of claims 1 to 4, characterized in that: In the step S1, the stirring speed is 500 rpm to 1000 rpm, the reaction time is 1 to 5 min, and the pH range is 2 to 5.

6. The method for producing ultrafine copper-based pre-alloyed powder according to any one of claims 1 to 5, characterized in that: In step S2, the copper salt solution includes at least one of the following materials: copper sulfate, copper chloride, copper nitrate, and copper acetate, the copper mass concentration is 40 g / L to 60 g / L, and a surfactant is added.

7. The method for producing ultrafine copper-based pre-alloyed powder according to claim 6, characterized in that: The surfactant includes sodium dodecyl sulfate with a concentration of 0.5 g / L to 2 g / L.

8. The method for producing ultrafine copper-based pre-alloyed powder according to any one of claims 1 to 7, characterized in that: In the step S2, the mass concentration, introduction time and reaction time of the copper salt solution are controlled so that the copper coating thickness is 20nm to 1000nm and the particle size is 10nm to 50μm.

9. The method for producing ultrafine copper-based pre-alloyed powder according to claim 8, characterized in that: In step S2, the copper salt solution is introduced for 1 to 5 minutes, the replacement reaction time is 1 to 5 minutes, and the replacement reaction temperature ranges from 20°C to 60°C.

10. The method for producing ultrafine copper-based pre-alloyed powder according to claim 9, characterized in that: In the step S3, washing includes centrifugal filtration, and drying includes one of the following methods: drying reduction, vacuum drying, and freeze drying, and the drying time is 2 to 10 hours.

Citation Information

Patent Citations

  • Core-shell structure copper-coated iron nanometer composite powder and preparation method and application thereof

    CN105251996A

  • Production of iron composite powder with copper coating

    CN1817509A

  • Superfine iron powder passivation method

    CN1936066A